Strategi Analisis SWOT dalam Pengelolaan Media Pembelajaran Berbasis ICT untuk Pendidikan Non-Formal: Studi Kasus Pusat Kegiatan Belajar Masyarakat di Jawa Barat - Astari; Muhamad Thaherudin; Rahmat Nurcahyo (Universitas La Tansa Mashiro, 2024)
Education development in Indonesia continues to advance, but the dropout rate, especially in West Java, is still high. This research explores the application of SWOT strategies in the management of ICT-based learning media in non-formal education, focusing on PKBM in West Java. The study covered three PKBMs in West Java, namely PKBM Bina Mandiri (Cimahi City), PKBM Mekarsari (West Bandung Regency), and PKBM An-Nur (Ibun District, Bandung Regency), using a descriptive approach with a questionnaire followed by 7 managers and 491 students. Data was analyzed using IFE, EFE, IE, SWOT, and QSPM matrices. The total IFE score was 2.45 and EFE was 2.00, placing PKBM in cell V (growth and stability position). Alternative strategies were arranged using the SWOT matrix, and strategy priorities were determined. The results show the highest priority strategy is a collaboration with other institutions to utilize a more complete ICT infrastructure without huge costs. Improving ICT infrastructure (TAS 6.25) ranked second, it is important to ensure the availability of devices and the internet. Educator competency development with a TAS of 5.85 is also significant, although slightly lower in priority.